The value of fecal calprotectin as a marker of intestinal inflammation in patients with ulcerative colitis - İbrahim Koral ÖNAL,; Yavuz Beyazıt,; Burçin ŞENER,; Burak SAVUK,; Diğdem ÖZER ETİK,; Abdurrahim SAYILIR,; Erkin Öztaş,; Serkan Torun,; Yasemin ÖZDERİN ÖZİN,; Bilge TUNÇ DEMİREL,; Aysel ÜLKER,; Ülkü DAĞLI, (Turkish Journal of Gastroenterology, 2019)
-